Cytotoxic tirucallane triterpenes from the stem of luvunga scandens - Al Zikri, Putri Nurhidayah; Bakhtiar, M. Taher; Darnis, Deny Susanti; Rezali, Mohd Fazlin; Read, Roger W; Sohrab, Md. Hossain; Hasan, Choudhury Mahmood; Ahmad, Farediah (Sociedade Brasileira de Farmacognosia, 2014)
Two tirucallane triterpenes, namely flindissol (1) and 3-oxotirucalla-7,24-dien-21-oic-acid (2), were isolated from the dichloromethane extract of the stem of Luvunga scandens (Roxb.) Buch-Ham ex Wight & Arn, Rutaceae. This is the first report of their isolation from this plant. Their structures were constructed by high resolution mass and 2D NMR spectroscopic data. The cytotoxic potential of the two pure compounds 1 and 2 were determined by MTT assay against human breast adenocarcinoma cell line (MCF-7). Compounds 1 and 2 showed potent cytotoxicity against MCF-7 cell line with IC50 values of 13.8 μM and 27.5 μM, respec- tively. This result suggested their potential activity as antitumor agents.